Presumptive asymptomatic COVID-19 carriers’ estimation and expected person-to-person spreading among repatriated passengers returning from China (2020)
Over the last 10 weeks the COVID-19 epidemic has exceeded 10 to 32 times the total number of confirmed SARS and MERS cases respectively. This has forced several countries around the world to establish extraordinary plans in terms of Public Health in order to prevent global expansion, including logistic design and guidelines with high security standards to repatriate citizens residing in China [1,2]. We believe that the information published daily in scientific documents as in gray material from government entities may be extremely valuable for estimating the pooled proportion of suspected asymptomatic carriers for COVID-19 (PAC-COVID-19). It is also possible to determine the number of PAC-COVID-19 during a repatriation plan by adjusting to the current R0 in Wuhan, to estimate the frequency of returnees in whom the infection could possibly spread, in context of a positive symptomatic returnee for COVID- 19. Therefore, herein we did so including the building of an online calculator to estimate the presumptive asymptomatic COVID-19 carriers.